Characteristics of Flame Shapes and Map For LPG and Hydrogen Inverse Confined Diffusion Flames at High Level of Fuel Excess - Yazid Bindar; Anton Irawan (Department of Chemical Engineering, Universitas Gadjah Mada, 2012)
A combustion flame can be generated by locating the air jet supply inside the fuel jet supply. This flame is referred as an inverse diffusion flame. The size and structure of inverse diffusion flame were studied experimentally. The experiment was conducted for LPG and Hydrogen fuels. The inlet fuel and air flow rates are supplied at high level of fuel excess for its combustion reaction. These two fuels generated the flame shape having two parts. At lower part, the flame is wider and serves as a base of the flame. The upper part is longer and acts as a flame tower. The base flame was a weak flame resulted by a rich fuel-air mixture. The tower flame is formed by mixing between the entrained fuel and the air. The flame length decreases with the increase on the momentum ration between fuel and air. The flame height correlates to the fuel and air Reynold number ratio, Refu/Rea. The development of the flame shapes from continues to strong base-tower flame shape is mapped by air and fuel inlet momentum rate. Very low fuel and air momentum rates result laminar flame and continuous shapes. The turbulent flames having base-tower shape are formed at high air momentum rate. The oxygen profiles shows that the oxygen concentration decays from the burner tip, vanishes at some distance from the burner tip and increase again after this distance. The hydrogen is completely consumed before the flame tip is reached